Dynamics of export imports oil and gas and non-oil and gas to indonesia's foreign exchange reserve: a vector autoregressive approach - Panji Kusuma Prasetyanto; Dinar Melani Hutajulu; Ryan Apriyadi (FORUM EKONOMI, 2022)
Foreign exchange reserves can be interpreted as a number of foreign currencies that are kept by the central bank to meet development financing needs and other country's dependents, namely export financing and foreign debt financing or other activities. Indonesia's foreign exchange reserves in the last ten years from January 2010 to January 2021 fluctuated, but experienced an upward trend. Oil and gas exports decreased by 7.11 percent and non-oil and gas exports decreased by 13.24 persen. Meanwhile, oil and gas imports increased by 4.73 percent and non-oil and gas imports decreased by 9.00 percent. The decline in Indonesia's oil and gas and non-oil and gas exports by category of goods in January 2021 compared to December 2020. This study aims to identify the relationship, shock response and variation between oil and gas and non-oil and gas imports and exports in foreign exchange reserves during January 2010 to January 2021. The variable in this study is the position of foreign exchange reserves, exports of oil and gas, exports of non-oil and gas, imports of oil and gas and imports of non-oil and gas. This study uses secondary data obtained from the official website of Bank Indonesia (BI) during January 2010 to January 2021. Data analysis uses the Vector Error Correction Model (VECM) analysis method. Granger Causality Test results show that there is a one-way relationship between EMI and ENM variables on PCD. While the other variables do not have a relationship. The average shock response occurred at the beginning and the middle of the next 12 periods, except for the shock response of non-oil and gas imports to the position of reserve reserves which tended to be stable. At the end of the next 12 periods, the contribution of PCD in explaining PCD Diversity itself has decreased by 80.97 percent, followed by IMI at 6.10 percent, INM at 4.98 percent, EMI at 4.67 percent and ENM at 3.26 persen